Antigua and Barbuda : Report on Observance of Standards and Codes-Basel Core Principles for Effective Banking Supervision--Offshore Banking. (IMF Staff Country Reports; Country Report ;, 2004)
The report on the Antigua and Barbuda's Observance of Standards and Codes on Basel Core Principles for Effective Banking Supervision is examined. Aggregated assets reported by the offshore banking sector totaled about USD 3.0 billion, equivalent in size to about four times the GDP, as on December 2002. The largest bank represents 61 percent of the sector's aggregated assets, highlighting an important degree of concentration. Investment portfolios represent the bulk of banks' assets and are predominantly composed of government and corporate bonds and equities.